PREVALENCE OF GESTATIONAL DIABETES MELLITUS IN THE SPECIAL REGION OF YOGYAKARTA - Windarwati Windarwati; Rukmono Siswishanto; Wirimena Hurimah; Primalia Sulistiowati; Dian Riski Ariesta; Valentin Widri Enggal; Himawan Sartono; Mutiara Nugraheni (MEDIKORA, 2023)
Gestational Diabetes Mellitus (GDM) is glucose intolerance when first detected during pregnancy. The prevalence of DMG in the last 20 years has significantly increased. The high prevalence of GDM has implications for maternal and child health. Mother has gestational hypertension and preeclampsia. Babies born are at risk for macrosomia, shoulder dystocia, and neonatal hypoglycemia. This study aims to see the prevalence of DMG in the Special Region of Yogyakarta. This study is an analytic observational study with a cross-sectional design. The study population was pregnant women with a gestational age of 24-28 weeks who checked themselves at the puskesmas in Yogyakarta. The research time is September 2018 to March 2019. The data analysis used is the Chi Square test. This prevalence study was conducted using the criteria of the World Health Organization (WHO), IADPSG/American Diabetes Association (ADA), NICE and Diabetes in Preganancy in India (DIPSI). The highest prevalence of DMG in the study was found in the NICE diagnostic criteria with a value of 14.9% then the DIPSI criteria 12.6%, IADPSG 12.1% and WHO 11.7%.